Rare earth magnet and method for producing the same

By nanocrystallizing the main phase in the R-Fe-B system rare earth magnet and adding La and Co, the problems of insufficient residual magnetization and poor squareness at high temperatures are solved, and performance optimization and high-temperature environmental adaptability of the motor are achieved.

CN114388211BActive Publication Date: 2025-02-14TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111234597.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-22
Filing Date
2021-10-22
Publication Date
2025-02-14
Estimated Expiration
2041-10-22

AI Technical Summary

Technical Problem

The existing R-Fe-B-based rare earth magnets have insufficient residual magnetization at high temperatures and have poor squareness, making it difficult to meet the needs of motors in high temperature environments.

Method used

The generation of phases with an RFe2 type crystal structure is suppressed by nanocrystalization in a rare earth magnet and containing a predetermined amount of La during the manufacturing process, while increasing the content of Co to improve the high-temperature magnetic characteristics.

Benefits of technology

The residual magnetization at high temperature and the optimization of squareness are achieved, and the performance requirements of the motor in high temperature environment are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114388211B_ABST
    Figure CN114388211B_ABST
Patent Text Reader

Abstract

Provided are an R-Fe-B rare earth magnet having excellent squareness and magnetic properties at high temperatures, especially excellent residual magnetization at high temperatures, and a method for manufacturing the same. The present invention discloses a rare earth magnet and a method for manufacturing the same, wherein the rare earth magnet comprises a main phase (10) and a grain boundary phase (20) existing around the main phase (10). The rare earth magnet disclosed in the present invention has an overall composition in terms of molar ratio represented by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v Indicates that, R 1 is the specified rare earth element, M 1 is a specified element, and 0≤x≤0.1, 12.0≤y≤20.0, 0.1≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0. The main phase (10) has R2Fe 14 In the B-type crystal structure, the average grain size of the main phase (10) is less than 1 μm, and in the grain boundary phase (20), the volume ratio of the phase having the RFe2 type crystal structure relative to the grain boundary phase (20) is less than 0.40.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a rare earth magnet and a method for producing the same. In particular, the present disclosure relates to an R—Fe—B system rare earth magnet (where R is a rare earth element) and a method for producing the same. Background Art

[0002] R-Fe-B rare earth magnets have a main phase and a grain boundary phase that exists around the main phase. 14 A magnetic phase with a B-type crystal structure. This main phase can provide high residual magnetization. Therefore, R—Fe—B rare earth magnets are often used in motors.

[0003] When permanent magnets such as R-Fe-B rare earth magnets are used in motors, the permanent magnets are placed in an external magnetic field environment that changes periodically. Therefore, the permanent magnets will be demagnetized (demagnetized) due to the increase in the external magnetic field. When permanent magnets are used in motors, it is required that they do not demagnetize as much as possible relative to the increase in the external magnetic field. The demagnetization curve represents the degree of demagnetization relative to the increase in the external magnetic field, and the demagnetization curve that meets the above requirements has a square shape. Therefore, meeting the above requirements is called excellent squareness.

[0004] Since the motor generates heat during operation, the permanent magnets used in the motor are required to have high residual magnetization at high temperatures. In this specification, the term "high temperature" in relation to magnetic properties refers to a temperature in the range of 100 to 200°C, particularly 140 to 180°C.

[0005] As R of R-Fe-B rare earth magnets, Nd is mainly selected, but due to the rapid popularization of electric vehicles, etc., there is a concern that the price of Nd will soar. Therefore, the use of cheap light rare earth elements has also been studied. For example, Patent Document 1 discloses an R-Fe-B rare earth magnet, in which Ce and La, which are light rare earth elements, are selected as R of the R-Fe-B rare earth magnet. In addition, for example, Patent Document 2 discloses an R-Fe-B rare earth magnet, in which a part of Nd as R of the R-Fe-B rare earth magnet is replaced by Ce, and a part of Fe is replaced by Co.

[0006] Prior Art Literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 61-159708

[0009] Patent Document 2: International Publication No. 2014 / 196605 Summary of the invention

[0010] When a light rare earth element is simply selected as R as in the R-Fe-B rare earth magnet disclosed in Patent Document 1, the magnetic properties are degraded. When a portion of Fe is replaced with a small amount of Co as in the R-Fe-B rare earth magnet disclosed in Patent Document 2, it is known that the corrosion resistance is improved. In addition, it is generally known that the inclusion of Co is effective in improving the magnetic properties at high temperatures, especially the residual magnetization at high temperatures. However, the inclusion of Co deteriorates the squareness.

[0011] The present disclosure is made to solve the above-mentioned problems. An object of the present disclosure is to provide an R—Fe—B rare earth magnet having excellent squareness and magnetic properties at high temperatures, especially residual magnetization at high temperatures, and a method for producing the same.

[0012] The present inventors have repeatedly conducted intensive research to achieve the above-mentioned purpose, and have thus completed the rare earth magnet and the method for producing the same disclosed in the present invention. The rare earth magnet and the method for producing the same disclosed in the present invention include the following aspects.

[0013] <1> A rare earth magnet comprising a main phase and a grain boundary phase existing around the main phase,

[0014] In terms of molar ratio, the overall composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v (Among them, R 1 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn and inevitable impurity elements, and 0≤x≤0.1, 12.0≤y≤20.0, 0.1≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0. ) indicates,

[0015] The main phase has R2Fe 14 The crystal structure of type B (where R is a rare earth element) is

[0016] The average particle size of the main phase is less than 1 μm, and

[0017] In the grain boundary phase, the volume ratio of the phase having the RFe2 type crystal structure relative to the grain boundary phase is 0.40 or less.

[0018] <2> A rare earth magnet comprising a main phase and a grain boundary phase existing around the main phase,

[0019] In terms of molar ratio, the overall composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v ·(R 2 (1-s) M 2 s ) t (Among them, R 1 and R 2 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn, and unavoidable impurity elements, M 2 For R 2 Alloyed metal elements other than rare earth elements and inevitable impurity elements, and 0≤x≤0.1, 12.0≤y≤20.0, 0.1≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0, 0.05≤s≤0.40, 0.1≤t≤10.0. ) indicates,

[0020] The x and the z satisfy z≤2x+0.2,

[0021] The main phase has R2Fe 14 The crystal structure of type B (where R is a rare earth element) is

[0022] The average particle size of the main phase is less than 1 μm, and

[0023] In the grain boundary phase, the volume ratio of the phase having the RFe2 type crystal structure relative to the grain boundary phase is 0.40 or less.

[0024] <3> According to the rare earth magnet described in item <2>, t satisfies 1.0≤t≤2.5.

[0025] <4> The rare earth magnet according to item <2> or <3>, wherein R 2 is one or more elements selected from Nd and Tb, and the M 2 It is Cu and inevitable impurity elements.

[0026] <5> The rare earth magnet according to any one of <1> to <4>, wherein R1 is one or more elements selected from Nd and Pr, and the M 1 It is one or more elements selected from Ga, Al and Cu, and inevitable impurity elements.

[0027] <6> A method for manufacturing a rare earth magnet, which is the method for manufacturing a rare earth magnet described in <1>, comprising the following steps:

[0028] A melt having the following composition is prepared, wherein the composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v (Among them, R 1 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn and inevitable impurity elements, and 0≤x≤0.1, 12.0≤y≤20.0, 0.1≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0. ) represents;

[0029] The melt was heated to 5×10 5 ~5×10 7 Cooling at a rate of °C / sec to obtain a magnetic ribbon or a magnetic sheet; and

[0030] The magnetic ribbon or the magnetic sheet is pressure-sintered to obtain a sintered body.

[0031] <7> The method for producing a rare earth magnet according to item <6>, wherein the magnetic ribbon or the magnetic sheet is pressure-sintered at 550 to 750°C.

[0032] <8> The method for manufacturing a rare earth magnet according to item <6> or <7>, further comprising the step of subjecting the sintered body to hot plastic processing.

[0033] <9> The method for producing a rare earth magnet according to any one of <6> to <8>,

[0034] The x and the z satisfy z≤2x+0.2, and the method further includes the following steps:

[0035] Prepare a modified material having the following composition, wherein the composition is represented by the formula R 2 (1-s) M 2s (Among them, R 2 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 2 For R 2 Alloyed metal elements other than rare earth elements and inevitable impurity elements, and 0.05≤s≤0.40. ) indicates; and

[0036] The modifying material is diffused and infiltrated into the sintered body.

[0037] <10> The method for producing a rare earth magnet according to item <9>, wherein the diffusion infiltration is performed at 550 to 750°C.

[0038] <11> The method for producing a rare earth magnet according to item <9> or <10>, wherein the R 2 for Nd and Tb, and the M 2 It is Cu and inevitable impurity elements.

[0039] <12> The method for producing a rare earth magnet according to any one of <6> to <11>, wherein the R 1 is one or more elements selected from Nd and Pr, and the M 1 It is one or more elements selected from Ga, Al and Cu, and inevitable impurity elements.

[0040] According to the present disclosure, by nano-crystallizing the main phase and optionally containing a specified amount of La as a part of R, the formation of a phase with an RFe2 type crystal structure that impairs the squareness is suppressed, and Co is contained, thereby providing an R-Fe-B rare earth magnet with improved high-temperature residual magnetization and a method for manufacturing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is an explanatory diagram schematically showing the structure of the rare earth magnet disclosed in the present invention.

[0042] Figure 2 This is an explanatory diagram schematically showing a cooling device used in the liquid rapid cooling method.

[0043] Figure 3 This is an explanatory diagram schematically showing a cooling device used in the strip casting method.

[0044] Figure 4 This is a graph showing the demagnetization curve of the sample of Example 2.

[0045] Figure 5 This is a graph showing the demagnetization curve of the sample of Comparative Example 3.

[0046] Figure 6This is a graph showing the relationship between the molar ratio x of La and the molar ratio z of Co for the samples of Examples 1 to 10 and Comparative Examples 1 to 4 (samples without a diffusion-permeation modifying material).

[0047] Figure 7 This is a graph showing the relationship between the molar ratio x of La and the molar ratio z of Co for the samples of Examples 11 to 17 and Comparative Examples 5 to 8 (samples in which the modifying material was diffused and infiltrated).

[0048] Figure 8 This is a diagram schematically showing the structure of a conventional rare earth magnet.

[0049] Description of Reference Numerals

[0050] 10 Main phase

[0051] 20 Grain boundary phase

[0052] 22 Adjacent part

[0053] 24 Three Points

[0054] 26 Phases with RFe2-type crystal structures

[0055] 50 Liquid quenching device

[0056] 51 Injection Nozzle

[0057] 52 Heater

[0058] 53 Cooling roller

[0059] 54 Magnetic Strip

[0060] 55 Magnetic Sheet

[0061] 70 Strip casting device

[0062] 71 Melting Furnace

[0063] 72 Melt

[0064] 73 Tundish

[0065] 74 Cooling roller

[0066] 75 Magnetic Alloy

[0067] 100 Rare earth magnet disclosed in the present invention

[0068] 200 Previous rare earth magnets DETAILED DESCRIPTION

[0069] Hereinafter, embodiments of the rare earth magnet and the method for producing the same according to the present disclosure will be described in detail. Note that the embodiments described below do not limit the rare earth magnet and the method for producing the same according to the present disclosure.

[0070] The findings obtained by the present inventors with respect to improving squareness and magnetic properties at high temperatures, particularly residual magnetization at high temperatures, will be described with reference to the drawings. Figure 1 This is an explanatory diagram schematically showing the structure of the rare earth magnet disclosed in the present invention. Figure 8 This is a diagram schematically showing the structure of a conventional rare earth magnet.

[0071] R-Fe-B rare earth magnets are made by 14 The theoretical composition of B (R is 11.8 mol%, Fe is 82.3 mol%, and B is 5.9 mol%). The molten metal containing a large amount of R solidifies, thereby stably obtaining R2Fe 14 In the following description, it is sometimes compared with R2Fe 14 The theoretical composition of B contains a large amount of R in the melt called "R-rich melt". 14 The B-type crystal structure is called "R2Fe 14 Phase B".

[0072] If the R-rich melt is solidified, Figure 1 and Figure 8 As shown, a structure having a main phase 10 and a grain boundary phase 20 existing around the main phase 10 can be obtained. The grain boundary phase 20 has: an adjacent portion 22 where two main phases 10 are adjacent, and a triple point 24 surrounded by three main phases 10. In the conventional rare earth magnet 200, a phase 26 having an RFe2 type crystal structure exists more in the adjacent portion 22 of the grain boundary phase 20. The phase having an RFe2 type crystal structure is a ferromagnetic phase, and when there are many phases having an RFe2 type crystal structure in the grain boundary phase 20, the squareness is reduced.

[0073] R-Fe-B rare earth magnets include sintered magnets and hot-plastic processed magnets. The sintered magnets are obtained by sintering magnetic powders with a main phase particle size of 1 to 10 μm at a high temperature of 900 to 1100°C or higher without pressure, and the hot-plastic processed magnets are obtained by sintering (hot pressing) magnetic ribbons or magnetic flakes with a nano-crystallized main phase at a low temperature of 550 to 750°C. In order to impart anisotropy to the sintered magnets, the magnetic powder is molded in a magnetic field to obtain a pressed powder body, and the pressed powder body is sintered without pressure. Even if the magnetic ribbons or magnetic flakes with a nano-crystallized main phase are molded in a magnetic field to obtain a pressed powder body, it is difficult to impart anisotropy because the main phase is excessively fine. Therefore, the sintered body obtained by pressure sintering the magnetic ribbons or flakes is subjected to hot plastic processing to impart anisotropy.

[0074] The magnetic powder having a main phase particle size of 1 to 10 μm is obtained by pulverizing a magnetic ribbon or flake obtained by rapidly cooling a molten metal having a composition of an R-Fe-B rare earth magnet by a strip casting method or the like. The magnetic ribbon or flake having a nano-crystallized main phase is obtained by ultra-rapidly cooling a molten metal having a composition of an R-Fe-B rare earth magnet by a liquid quenching method or the like.

[0075] Figure 8 The phase 26 having an RFe2 type crystal structure as shown is easily generated when a magnetic ribbon or flake having a main phase particle size of 1 to 10 μm is obtained. In addition, the sintered body obtained by crushing a magnetic ribbon or flake having a main phase particle size of 1 to 10 μm and sintering the obtained crushed material without pressure has low coercive force (coercive force) in the original state, so most of them are subjected to heat treatment (hereinafter, such heat treatment is referred to as "optimal heat treatment"). Regarding the conditions of the optimal heat treatment, as a typical example, the sintered body is kept at 850 to 1000°C for 50 to 300 minutes and then cooled to 450 to 700°C at a rate of 0.1 to 5.0°C / min. The phase 26 having an RFe2 type crystal structure is easily generated during the optimal heat treatment, especially during the cooling process of the optimal heat treatment.

[0076] If part of the Fe of the R-Fe-B rare earth magnet is replaced by Co, the Curie temperature rises, so the magnetic properties at high temperatures, especially the residual magnetization at high temperatures, are improved. On the other hand, if part of the Fe of the R-Fe-B rare earth magnet is replaced by Co, a phase with an RFe2 type crystal structure is easily generated.

[0077] However, if Figure 1 When the super-quenched structure is formed to the extent that the main phase 10 is nano-crystallized as shown in the R-Fe-B rare earth magnet 100 of the present disclosure, even if a part of Fe is replaced by Co, the generation of the phase having the RFe2 type crystal structure can be suppressed. As a result, in the R-Fe-B rare earth magnet 100 of the present disclosure, the phase 26 having the RFe2 type crystal structure does not exist in the grain boundary phase 20, or even if it exists, its amount is very small. As a result, the squareness of the R-Fe-B rare earth magnet 100 of the present disclosure is improved. In addition, since the phase 26 having the RFe2 type crystal structure easily becomes the starting point of magnetization reversal, if the phase 26 having the RFe2 type crystal structure does not exist, or even if it exists, its amount is very small, it also helps to improve the coercive force.

[0078] Furthermore, if the R-Fe-B rare earth magnet 100 disclosed in the present invention contains La, the generation of a phase having an RFe2 type crystal structure can be further suppressed. In order to improve the coercive force, the R-Fe-B rare earth magnet disclosed in the present invention diffuses and infiltrates a melt of a low melting point alloy such as an Nd-Cu alloy as a modifying material. Thus, the melt of the modifying material can be diffused and infiltrated at a temperature that does not coarsen the nanocrystallized main phase. However, such a diffusion and infiltration temperature is a temperature at which a phase 26 having an RFe2 type crystal structure is easily generated in the grain boundary phase 20. Therefore, if the R-Fe-B rare earth magnet 100 disclosed in the present invention contains La, the generation of a phase 26 having an RFe2 type crystal structure during diffusion and infiltration can be further suppressed.

[0079] When a light rare earth element is selected as R as disclosed in Patent Document 1, Ce is generally included in the selection. However, since Ce promotes the formation of a phase having an RFe2 type crystal structure, in the rare earth magnet disclosed in the present invention, La is selected as the light rare earth element in addition to a very small amount of Ce contained as an inevitable impurity element.

[0080] In the R-Fe-B rare earth magnet disclosed in Patent Document 2, the main phase is nano-crystallized. Moreover, a portion of Fe is replaced by Co. However, in the R-Fe-B rare earth magnet disclosed in Patent Document 2, a portion of Fe is replaced by Co mainly to improve corrosion resistance, and the replacement rate is small. Therefore, the generation of phase 26 having an RFe2 type crystal structure rarely becomes a problem. On the other hand, in order to improve the magnetic properties at high temperatures, especially the residual magnetization at high temperatures, it is necessary to contain more Co as in the R-Fe-B rare earth magnet 100 disclosed in the present invention.

[0081] The R-Fe-B rare earth magnet disclosed in the present invention contains Co at a relatively high prescribed ratio (molar ratio) in order to improve the residual magnetization at high temperatures. Since Co is contained at a relatively high prescribed ratio (molar ratio), it becomes easy to generate phase 26 having an RFe2 type crystal structure, and the squareness is reduced. However, when obtaining a magnetic ribbon or a thin sheet, ultra-rapid cooling is performed to the extent that the main phase is nano-crystallized to suppress the generation of phase 26 having an RFe2 type crystal structure. In addition, by containing a prescribed ratio of La in the R-Fe-B rare earth magnet disclosed in the present invention, it is possible to further suppress the generation of phase 26 having an RFe2 type crystal structure during the manufacture of the magnetic ribbon or the magnetic thin sheet and during the processing of the magnetic ribbon or the magnetic thin sheet, thereby improving the squareness.

[0082] The constituent elements of the rare earth magnet and the method for producing the same according to the present disclosure based on these findings will be described below.

[0083] [Rare earth magnets]

[0084] First, the constituent elements of the rare earth magnet of the present disclosure will be described.

[0085] like Figure 1 As shown, the rare earth magnet 100 of the present disclosure includes a main phase 10 and a grain boundary phase 20. Hereinafter, the overall composition of the rare earth magnet 100 of the present disclosure and the main phase 10 and the grain boundary phase 20 will be described.

[0086] 〈Overall composition〉

[0087] The overall composition of the rare earth magnet 100 of the present disclosure will be described. The overall composition of the rare earth magnet 100 of the present disclosure refers to the composition of all the main phases 10 and the grain boundary phases 20 combined.

[0088] The overall composition of the rare earth magnet disclosed in the present invention, in terms of molar ratio, is represented by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v Or (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v ·(R 2 (1-s) M 2 s ) t Indicates. Formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v represents the overall composition when the permeation modifying material is not diffused. 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v ·(R 2(1-s) M 2 s ) t = represents the overall composition of the diffusion permeation modification material. In this formula, the first half (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v Indicates the composition of the sintered body (rare earth magnet precursor) before the diffusion-infiltration modification material is formed. The latter part (R 2 (1-s) M 2 s ) t Indicates the composition derived from the modified material.

[0089] In the case of diffusion-infiltration of the modifying material, 100 mol parts of the sintered body is used as a rare earth magnet precursor and t mol parts of the modifying material are diffused and infiltrated into the interior of the sintered body, thereby obtaining (100+t) mol parts of the rare earth magnet of the present disclosure.

[0090] In the formula representing the overall composition of the rare earth magnet disclosed in the present invention, R 1 The total of La is y molar parts, the total of Fe and Co is (100-y-w-v) molar parts, B is w molar parts, and M 1 Therefore, the total of these is y molar parts + (100-y-w-v) molar parts + w molar parts + v molar parts = 100 molar parts. 2 and M 2 The total is t molar parts.

[0091] In the above formula, R 1 (1-x) La x Meaning: relative to R 1 The total amount of R and La is (1-x) in molar ratio. 1 , there is x La. Similarly, in the above formula, Fe (1-z) Co z This means that, relative to the total amount of Fe and Co, in terms of molar ratio, there are (1-z) Fe and z Co. Similarly, in the above formula, R 2 (1-s) M 2 s Meaning: relative to R 2 and M 2 The total, in terms of molar ratio, of R2 , there exists an M of s 2 .

[0092] In the above formula, R 1 and R 2 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho. Nd is neodymium, Pr is praseodymium, Gd is gadolinium, Tb is terbium, Dy is dysprosium, and Ho is holmium. Fe is iron. Co is cobalt. B is boron. M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn, and inevitable impurity elements. Ga is gallium, Al is aluminum, Cu is copper, Au is gold, Ag is silver, Zn is zinc, In is indium, and Mn is manganese. 2 For R 2 Alloying metal elements other than rare earth elements and inevitable impurity elements.

[0093] In this specification, unless otherwise specified, rare earth elements refer to 17 elements, namely, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Among them, unless otherwise specified, Sc, Y, La, and Ce are light rare earth elements. In addition, unless otherwise specified, Pr, Nd, Pm, Sm, and Eu are medium rare earth elements. Moreover, unless otherwise specified, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu are heavy rare earth elements. Furthermore, generally, the scarcity of heavy rare earth elements is high, and the scarcity of light rare earth elements is low. The scarcity of medium rare earth elements is between that of heavy rare earth elements and that of light rare earth elements. Furthermore, Sc is scandium, Y is yttrium, La is lanthanum, Ce is cerium, Pr is praseodymium, Nd is neodymium, Pm is promethium, Sm is samarium, Eu is europium, Gd is gadolinium, Tb is terbium, Dy is dysprosium, Ho is holmium, Er is erbium, Tm is thulium, Yb is ytterbium, and Lu is lutetium.

[0094] Hereinafter, the constituent elements of the rare earth magnet of the present disclosure represented by the above-mentioned formula will be described.

[0095] 〈R 1 〉

[0096] R 1 It is an essential component in the rare earth magnet disclosed in the present invention. As mentioned above, R 1 It is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho. 1 Is the main phase (with R2Fe 14 The phase of the B-type crystal structure (hereinafter sometimes referred to as "R2Fe 14 B phase".)) constituent elements. From the perspective of the balance between residual magnetization, coercive force and price, R1 Preferably, at least one element selected from Nd and Pr is used. 1 In the case of making Nd and Pr coexist, didymium can be used.

[0097] 〈La〉

[0098] La is an optional component in the rare earth magnet of the present disclosure. 1 Together for R2Fe 14 A constituent element of the B phase. The rare earth magnet disclosed in the present invention is manufactured using a magnetic ribbon or magnetic flake whose main phase is nanocrystallized. When manufacturing the magnetic ribbon or magnetic flake, by ultra-quenching the melt to the extent that the main phase is nanocrystallized, the generation of a phase having an RFe2 type crystal structure can be suppressed. If the melt contains La, the generation of a phase having an RFe2 type crystal structure can be further suppressed when manufacturing the magnetic ribbon or magnetic flake. In addition, if the magnetic ribbon or magnetic flake contains La, the generation of a phase having an RFe2 type crystal structure can be further suppressed in the process of manufacturing the rare earth magnet disclosed in the present invention from the magnetic ribbon or magnetic flake. As a result, by containing La, the squareness of the rare earth magnet disclosed in the present invention can be more easily improved. Although not bound by theory, it is believed that this is because La has a larger atomic diameter than other rare earth elements, and it is difficult to generate a phase having an RFe2 type crystal structure.

[0099] As described above, the rare earth magnet of the present invention has a main phase that has been nanocrystallized. Therefore, when the rare earth magnet of the present invention is used as a precursor to diffuse and infiltrate the modifying material into the precursor, the melt of a low melting point alloy such as an Nd-Cu alloy is diffused and infiltrated. At the diffusion and infiltration temperature at this time, it is easy to generate a phase with an RFe2 type crystal structure from the grain boundary phase, but by containing La in the grain boundary phase, the generation of the phase with the RFe2 type crystal structure can be further suppressed. In addition, if a modifying material containing heavy rare earth elements, especially Tb and Dy, is diffused and infiltrated, the magnetic disconnection (magnetic separation) effect between the main phases is large, but on the other hand, the heavy rare earth elements and Co diffused and infiltrated into the grain boundary phase are easy to generate a phase with an RFe2 type crystal structure. However, by containing La, the generation of the phase with the RFe2 type crystal structure can be suppressed, which is preferred.

[0100] 〈R 1 The molar ratio of La

[0101] As described above, La is not essential in the rare earth magnet of the present disclosure, but by containing La, the generation of a phase having an RFe2 type crystal structure can be further suppressed. 1The molar ratio of La to La will be described. When La is not contained, x is 0 in the formula representing the above overall composition.

[0102] In R-Fe-B rare earth magnets, La, as R, is difficult to generate R2Fe with Fe and B alone. 14 B phase. However, if La is selected as part of R, R2Fe can be generated. 14 B phase. In addition, La suppresses the generation of a phase having an RFe2 type crystal structure, and as a result, the squareness can be improved.

[0103] If even a little La is contained, the formation of a phase having an RFe2 type crystal structure can be suppressed. If x is greater than 0.01, it is confirmed that the formation of a phase having an RFe2 type crystal structure is suppressed in practice. From the viewpoint of suppressing the formation of a phase having an RFe2 type crystal structure, x can be greater than 0.02, greater than 0.025, greater than 0.03, greater than 0.04, or greater than 0.05. On the other hand, if x is less than 0.1, R2Fe is not given. 14 From this point of view, x can be less than 0.09, less than 0.08, or less than 0.07. In this way, even if the content of La is relatively low relative to R 1 The ratio (molar ratio) of the content of La is very small, and the effect of suppressing the generation of a phase having an RFe2 type crystal structure is also high. Although not bound by theory, it is believed that this is because, even if the La content is small in the rare earth magnet disclosed herein as a whole, La is difficult to become a constituent element of the main phase and is easily expelled into the grain boundary phase, thus easily contributing to suppressing the generation of a phase having an RFe2 type crystal structure in the grain boundary phase.

[0104] 〈R 1 Total content ratio of La>

[0105] In the above formula, R 1 The total content ratio of La is represented by y, and satisfies 12.0≤y≤20.0. The value of y is the content ratio of the rare earth magnet of the present disclosure relative to the case where the modified material is not diffused and infiltrated, and corresponds to mol % (atomic %).

[0106] If y is 12.0 or more, the αFe phase will not exist in large quantities, and a sufficient amount of the main phase (R2Fe 14B phase). From this viewpoint, y may be 12.4 or more, 12.8 or more, 13.0 or more, 13.2 or more, 13.4 or more, or 14.0 or more. On the other hand, if y is 20.0 or less, the grain boundary phase does not become excessive. From this viewpoint, y may be 19.0 or less, 18.0 or less, 17.0 or less, 16.0 or less, or 15.0 or less.

[0107] 〈B〉

[0108] B composition Figure 1 The main phase 10(R2Fe 14 B phase), which affects the existence ratio of the main phase 10 and the grain boundary phase 20.

[0109] The content ratio of B is represented by w in the above formula. The value of w is the content ratio of the rare earth magnet of the present disclosure relative to the case where the modified material is not diffused, and is equivalent to mol% (atomic%). If w is less than 20.0, a rare earth magnet in which the main phase 10 and the grain boundary phase 20 are properly present can be obtained. From this point of view, w can be less than 18.0, less than 16.0, less than 14.0, less than 12.0, less than 10.0, less than 8.0, less than 6.0, or less than 5.9. On the other hand, if w is more than 5.0, it is difficult to cause a large amount of production of Th2Zn 17 Type and / or Th2Ni 17 The crystal structure of the phase is as follows, which hinders the R2Fe 14 The B phase is rarely formed. From this viewpoint, w may be 5.2 or more, 5.4 or more, 5.5 or more, 5.7 or more, or 5.8 or more.

[0110] 〈M 1 〉

[0111] M 1 It is an element that can be contained within a range that does not impair the characteristics of the rare earth magnet disclosed in the present invention. 1 Inevitable impurity elements may be included. In this specification, the so-called inevitable impurity elements refer to impurity elements contained in the raw materials of rare earth magnets or impurity elements mixed in the manufacturing process, which cannot be avoided, or impurity elements that will significantly increase the manufacturing cost if they are avoided. Among the impurity elements mixed in the manufacturing process, elements that are included in the range that does not affect the magnetic properties are included according to the manufacturing situation. In addition, the inevitable impurity elements include R 1 Rare earth elements other than the rare earth elements selected for the purpose of reducing La and reducing Si are inevitably mixed therein due to the reasons mentioned above.

[0112] The element M that can be contained in the range not to impair the effects of the rare earth magnet and the method for producing the same disclosed herein is 1 , and may include one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn. As long as these elements are in the form of M 1 If the content of M is less than the upper limit, these elements will not substantially affect the magnetic properties. Therefore, these elements can be treated equally with unavoidable impurity elements. 1 , and may also contain unavoidable impurity elements. 1 , preferably one or more elements selected from Ga, Al and Cu and inevitable impurity elements.

[0113] In the above formula, M 1 The content ratio is represented by v. The value of v is the content ratio of the rare earth magnet of the present disclosure relative to the non-diffused infiltration modified material, which is equivalent to mol% (atomic%). If the value of v is 2.0 or less, the magnetic properties of the rare earth magnet of the present disclosure will not be impaired. From this point of view, v can be 1.5 or less, 1.0 or less, 0.65 or less, 0.6 or less, or 0.5 or less.

[0114] As M 1 It is impossible to completely eliminate Ga, Al, Cu, Au, Ag, Zn, In, Mn and inevitable impurity elements, so even if the lower limit of v is 0.05, 0.1, or 0.2, there is no problem in practical use.

[0115] 〈Fe〉

[0116] Fe is related to R 1 , La, B and Co described later together constitute the main phase (R2Fe 14 A part of Fe may be replaced by Co.

[0117] 〈Co〉

[0118] Co is an element that can replace Fe in the main phase and grain boundary phase. In this specification, unless otherwise specified, when Fe is recorded, it means that part of Fe can be replaced by Co. For example, R2Fe 14 Part of the Fe in the B phase is replaced by Co to form R2(Fe, Co) 14 Phase B.

[0119] In a phase having an RFe2 type crystal structure, part of Fe in the phase is replaced by Co. Although not bound by theory, for a phase having an RFe2 type crystal structure in which part of Fe is replaced by Co, such a phase is extremely unstable due to part of R being replaced by La. Therefore, in the rare earth magnet disclosed in the present invention, there is no phase having an RFe2 type crystal structure, or even if there is, its amount is very small.

[0120] By replacing part of Fe with Co, R2Fe 14 B phase changes to R2(Fe, Co) 14 Phase B improves the Curie temperature of the rare earth magnet of the present disclosure. As a result, the magnetic properties of the rare earth magnet of the present disclosure at high temperatures, especially the residual magnetization at high temperatures, are improved.

[0121] 〈Fe to Co molar ratio〉

[0122] If z is above 0.1, it is substantially possible to confirm the improvement of magnetic properties at high temperatures, especially residual magnetization at high temperatures, brought about by the rise in Curie temperature. From this viewpoint, z can be above 0.12, above 0.14, above 0.15, or above 0.16. On the other hand, if z is below 0.3, as long as the main phase is quenched to the extent that it is nano-crystallized when obtaining a magnetic ribbon or a magnetic sheet, the generation of a phase having a crystal structure of the RFe2 type can be suppressed. From this viewpoint, z can be below 0.28, below 0.26, below 0.24, below 0.22, or below 0.20. In addition, due to the high price of Co, it is preferably within the above range. Furthermore, when diffusing and penetrating the modified material, it is necessary to make the content ratio (molar ratio) of La and Co a specific relationship, which is explained below.

[0123] 〈Relationship between the molar ratio of La and Co〉

[0124] When the modified material is diffused and infiltrated, the content ratio (molar ratio) of La and Co is made to be in a specific relationship. In the formula representing the above-mentioned overall composition, the content ratio of La is represented by x, and the content ratio of Co is represented by z. As mentioned above, when the modified material is diffused and infiltrated, it becomes easy to generate a phase with an RFe2 type crystal structure. In addition, by containing Co, it becomes easy to generate a phase with an RFe2 type crystal structure. Therefore, if the existence ratio (molar ratio) of La is the same, it is necessary to reduce the content ratio of Co. It has been experimentally confirmed that z≤2x+0.2 is sufficient.

[0125] <Total content ratio of Fe and Co>

[0126] The total content ratio of Fe and Co is obtained by adding the R 1 , La, B and M1 The remaining portion except for the above is represented by (100-ywv). As mentioned above, the values ​​of y, w and v are the content ratios of the rare earth magnet of the present disclosure relative to the non-diffused infiltration modified material, so (100-ywv) is equivalent to mole % (atomic %). If y, w and v are set to the ranges described above, it can be obtained Figure 1 The main phase 10 and the grain boundary phase 20 are shown.

[0127] 〈R 2 〉

[0128] R 2 The element originates from the modifying material. The modifying material diffuses and permeates into the interior of the sintered body of the magnetic ribbon or magnetic sheet (the rare earth magnet of the present disclosure in which the modifying material is not diffused and permeated). The melt of the modifying material passes through Figure 1 The grain boundary phase 20 diffuses and penetrates.

[0129] R 2 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho. 2 In the case of coexistence of Nd and Pr, a mixture of didymium and praseodymium can be used. The modified material magnetically separates the main phases from each other to increase the coercive force. Therefore, among the above rare earth elements, R 2 , preferably containing heavy rare earth elements, especially Tb. 2 Preferably, it is one or more elements selected from Nd and Tb.

[0130] 〈M 2 〉

[0131] M 2 is with R 2 Alloying metal elements other than rare earth elements and inevitable impurity elements. 2 Is to make R 2 (1-s) M 2 s The melting point is lower than R 2 Alloy elements with melting points and unavoidable impurity elements. 2 , for example, one or more elements selected from Cu, Al, Co and Fe and inevitable impurity elements. 2 (1-s) M 2 s From the perspective of melting point, as M 2, preferably Cu. In addition, the so-called inevitable impurity elements refer to: impurity elements contained in raw materials or impurity elements mixed in the manufacturing process, which cannot be avoided, or impurity elements that will cause a significant increase in manufacturing costs in order to avoid their inclusion. Among the impurity elements mixed in the manufacturing process, the elements contained in the range that do not affect the magnetic properties are included according to the manufacturing situation. In addition, the inevitable impurity elements include R 2 Rare earth elements other than the selected rare earth elements are inevitably mixed due to the reasons mentioned above.

[0132] 〈R 2 and M 2 The molar ratio of

[0133] R 2 and M 2 Formed with the formula R 2 (1-s) M 2 s The modified material contains an alloy having a composition represented by a molar ratio. Furthermore, s satisfies 0.05≤s≤0.40.

[0134] If s is 0.05 or more, the melt of the modifying material can be diffused and infiltrated into the interior of the sintered body (the rare earth magnet of the present disclosure where the modifying material is not diffused and infiltrated) at a temperature that can avoid coarsening of the main phase. From this viewpoint, s is preferably 0.10 or more, and more preferably 0.15 or more. On the other hand, if s is 0.40 or less, the M remaining in the grain boundary phase of the rare earth magnet of the present disclosure after the modifying material is diffused and infiltrated into the interior of the sintered body (the rare earth magnet of the present disclosure where the modifying material is not diffused and infiltrated) is suppressed. 2 The content of s helps to suppress the reduction of residual magnetization. From this viewpoint, s can be 0.35 or less, 0.30 or less, 0.25 or less, 0.20 or less, or 0.18 or less.

[0135] <Molar ratio of elements derived from sintered body and elements derived from modified material>

[0136] As described above, in the case of a diffusion-infiltration modified material, the overall composition of the rare earth magnet disclosed in the present invention is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v ·(R 2 (1-s) M2 s ) t In this formula, the first half (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v Indicates the composition of the sintered body (rare earth magnet precursor) before the diffusion-infiltration modification material is formed. The latter part (R 2 (1-s) M 2 s ) t Indicates the composition derived from the modified material.

[0137] In the above formula, the ratio of the modifying material to 100 mol parts of the sintered body is t mol parts. That is, if t mol parts of the modifying material are diffused and infiltrated into 100 mol parts of the sintered body, 100 mol parts + t mol parts of the rare earth magnet of the present disclosure will be obtained. In other words, the rare earth magnet of the present disclosure is (100 + t) mol % ((100 + t) atomic %) relative to 100 mol % (100 atomic %) of the sintered body.

[0138] If t is 0.1 or more, it is substantially possible to confirm the effect of increasing the coercive force by magnetically dividing the main phase. From this point of view, t may be 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.8 or more, 1.0 or more, or 1.2 or more. On the other hand, if t is 10.0 or less, the residual M in the grain boundary phase of the rare earth magnet disclosed in the present invention is suppressed. 2 From this viewpoint, t may be 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, 4.0 or less, 3.0 or less, 2.0 or less, 1.8 or less, 1.6 or less, or 1.4 or less.

[0139] like Figure 1 As shown, the rare earth magnet 100 of the present disclosure includes a main phase 10 and a grain boundary phase 20. The main phase 10 and the grain boundary phase 20 will be described below.

[0140] 〈Main Phase〉

[0141] The main phase has R2Fe 14 The crystal structure of type B. R is a rare earth element. Let R2Fe 14B “type” is because elements other than R, Fe, and B can be included in the main phase (in the crystal structure) in substitutional and / or interstitial forms. For example, in the rare earth magnet of the present disclosure, part of Fe in the main phase is replaced by Co. Co can also exist in the main phase in interstitial form. Moreover, in the rare earth magnet of the present disclosure, part of any one of the elements R, Fe, Co, and B can also be replaced by M in the main phase. 1 Or, for example, in the main phase M 1 It can also exist in intermittent form.

[0142] The main phase is nano-crystallized. The so-called "main phase is nano-crystallized" means that the average particle size of the main phase is less than 1.0μm. The rare earth magnet disclosed in the present invention is obtained by pressure sintering a magnetic ribbon or magnetic flake whose main phase is nano-crystallized, as described later. The magnetic ribbon or magnetic flake is obtained by ultra-rapid cooling of the melt. If the melt is ultra-rapidly cooled to the extent that the main phase is nano-crystallized, the formation of a phase with an RFe2 type crystal structure can be suppressed. From this point of view, the average particle size of the main phase can be greater than 0.05μm, greater than 0.10μm, greater than 0.20μm, greater than 0.30μm, greater than 0.40μm, or greater than 0.50μm, and can be less than 0.90μm, less than 0.80μm, less than 0.70μm, or less than 0.60μm.

[0143] The "average particle size" is measured as follows. In a scanning electron microscope image or a transmission electron microscope image, a certain area observed from a direction perpendicular to the easy magnetization axis is defined. For the main phase existing in the certain area, many lines are drawn in a direction perpendicular to the easy magnetization axis, and the diameter (length) of the main phase is calculated from the distance between the points intersecting within the particles of the main phase (cutting method). When the cross section of the main phase is close to a circle, it is converted to the projection area equivalent circle diameter (projection area equivalent circle diameter). When the cross section of the main phase is close to a rectangle, it is converted by rectangular parallelepiped approximation. The distribution (particle size distribution) of the diameter (length) obtained in this way is D 50 The value is the average particle size.

[0144] 〈Grain boundary phase〉

[0145] like Figure 1 As shown, the rare earth magnet 100 of the present disclosure includes a main phase 10 and a grain boundary phase 20 existing around the main phase 10. As described above, the main phase 10 includes a R2Fe 14 The magnetic phase of the B-type crystal structure (R2Fe 14 B phase). On the other hand, the grain boundary phase 20 has R2Fe 14The phase with a crystal structure other than type B includes a phase with an unclear crystal structure. The so-called "unclear phase" is not limited by theory but means a phase (state) in which at least a part of the phase has an incomplete crystal structure and exists irregularly. Alternatively, it means a phase in which at least a part of such a phase (state) has almost no crystal structure, such as amorphous. Regarding the phase existing in the grain boundary phase 20, it has R2Fe 14 Phases with crystal structures other than type B and phases with unclear crystal structures are related to R2Fe 14 Compared with the phase phase of the B-type crystal structure, the abundance ratio of R is higher. Therefore, the grain boundary phase 20 is sometimes referred to as "R-rich phase", "rare earth element-rich phase" or "rare earth-rich phase".

[0146] like Figure 1 and Figure 8 As shown, the rare earth magnet 100 of the present disclosure and the conventional rare earth magnet 200 both include a main phase 10 and a grain boundary phase 20. In addition, the grain boundary phase 20 includes an adjacent portion 22 and a triple point 24.

[0147] When the molten metal having the composition of the rare earth magnet 100 of the present disclosure is solidified, and when the molten metal having the composition of the conventional rare earth magnet 200 is solidified, the residual liquid is present in the adjacent portion 22 and the triple point 24 when the main phase 10 is generated. However, when the molten metal having the composition of the rare earth magnet 100 of the present disclosure is solidified, and when the molten metal having the composition of the conventional rare earth magnet 200 is solidified, the phases generated by the solidification of the residual liquid are different.

[0148] When the molten metal having the composition of the conventional rare earth magnet 200 is solidified, it is rapidly cooled to such an extent that the main phase 10 becomes a micrometer level in size, so that a large number of phases having a RFe2 type crystal structure are generated in the adjacent portion 22. In addition to the phase having the RFe2 type crystal structure, the adjacent portion 22 also has phases having a crystal structure other than R2Fe 14 Crystal structures other than B-type and RFe2-type, and with R2Fe 14 The B-type crystal structure has a higher proportion of the phase than R. In the triple point 24, there are many phases with other than R2Fe 14 Crystal structures other than B-type and RFe2-type, and with R2Fe 14 The B-type crystal structure has a higher proportion of phase than R. In contrast, when a molten metal having the composition of the rare earth magnet 100 of the present disclosure is solidified, a large amount of R2Fe2O3 is generated in both the adjacent portion 22 and the triple point 24. 14 Crystal structures other than type B, and with R2Fe 14The B-type crystal structure phase has a higher existence ratio than the R-type phase. However, since the melt having the composition of the rare earth magnet 100 disclosed in the present invention is ultra-rapidly cooled to the extent that the main phase is crystallized to 10 nanometers, a phase having an RFe2-type crystal structure is not generated in the adjacent portion 22 and the triple point 24, or even if it is generated, its generation amount is very small.

[0149] The amount of existence (production amount) of the phase having an RFe2 type crystal structure is evaluated by the volume ratio of the phase having an RFe2 type crystal structure relative to the grain boundary phase. The volume ratio of the phase having an RFe2 type crystal structure is calculated as follows. The X-ray diffraction spectrum of the rare earth magnet disclosed in the present invention is subjected to Rietveld analysis to calculate the volume ratio of the phase having an RFe2 type crystal structure. In addition, the volume ratio of the main phase is calculated based on the content ratio of rare earth elements and boron. Moreover, in the rare earth magnet disclosed in the present invention, the phase other than the main phase is regarded as a grain boundary phase to calculate the volume ratio of the grain boundary phase. Based on these, (volume ratio of the phase having an RFe2 type crystal structure) / (volume ratio of the grain boundary phase) is calculated and used as the volume ratio of the phase having an RFe2 type crystal structure relative to the grain boundary phase.

[0150] In the rare earth magnet disclosed in the present invention, the volume ratio of the phase having the RFe2 type crystal structure relative to the grain boundary phase is 0.40 or less. Since the squareness will be impaired by the presence of the phase having the RFe2 type crystal structure, the volume ratio of the phase having the RFe2 type crystal structure is preferably as low as possible. Therefore, if the volume ratio is less than 0.40, less than 0.30, less than 0.22, less than 0.19, less than 0.14, less than 0.13, or less than 0.10, the squareness ratio becomes more than 0.6, and the squareness is excellent. On the other hand, from the perspective of squareness, it is ideal that the volume ratio of the phase having the RFe2 type crystal structure is 0. However, as long as the upper limit of the volume ratio of the phase having the RFe2 type crystal structure satisfies the above value, there is no problem in practical use even if the volume ratio of the phase having the RFe2 type crystal structure is more than 0.01, more than 0.02, more than 0.03, more than 0.04, or more than 0.05. Furthermore, the squareness ratio refers to Hr / Hc. Hc is the coercive force, and Hr is the magnetic field at 5% demagnetization. The magnetic field at 5% demagnetization means the magnetic field in the second quadrant of the hysteresis curve (demagnetization curve) when the magnetization decreases by 5% compared to the residual magnetization (magnetic field when the applied magnetic field is 0 kA / m).

[0151] [Manufacturing method]

[0152] Next, the method for producing the rare earth magnet of the present disclosure will be described.

[0153] The method for manufacturing a rare earth magnet disclosed in the present invention includes the steps of melt preparation, melt cooling and pressure sintering. The sintered body obtained by pressure sintering can be used as the rare earth magnet disclosed in the present invention, or the sintered body can be used as the rare earth magnet disclosed in the present invention after being subjected to thermoplastic processing. In addition, the sintered body before thermoplastic processing can be used as the rare earth magnet disclosed in the present invention after the modified material is diffused and infiltrated. Alternatively, the sintered body after thermoplastic processing can be used as the rare earth magnet disclosed in the present invention after the modified material is diffused and infiltrated. From the viewpoint of obtaining a rare earth magnet having anisotropy and excellent residual magnetization and coercive force, it is typically preferred to perform thermoplastic processing on the sintered body obtained by pressure sintering, and then diffuse and infiltrate the modified material into the sintered body after thermoplastic processing. In the case of performing thermoplastic processing and / or diffusion and infiltration of the modified material on the sintered body obtained by pressure sintering, in addition to the above-mentioned steps, thermoplastic processing and the steps of preparing the modified material and diffusion and infiltration are added. Each step is explained below.

[0154] 〈Metal Preparation〉

[0155] A melt having the following composition is prepared, wherein the composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v In this formula, about R 1 , La, Fe, Co, B and M 1 , and x, y, z, w, and v are the same as those described in the "[Rare Earth Magnet]" section. The amount of loss can also be estimated for elements that may be lost in subsequent processes.

[0156] 〈Metal Cooling〉

[0157] The melt having the above composition was heated to 5×10 5 ~5×10 7 ℃ / second and then cooled (ultra-rapid cooling). By cooling (ultra-rapid cooling) at such a speed, a magnetic ribbon or magnetic sheet having a nano-crystallized main phase and suppressing the generation of a phase having an RFe2 type crystal structure is obtained. The nano-crystallized main phase can also be obtained by nano-crystallizing the amorphous phase using the heat of pressure sintering when the amorphous magnetic ribbon or magnetic sheet is pressure-sintered, but in this case, a phase having an RFe2 type crystal structure is also generated in large quantities. If the cooling rate of the melt is 5×10 7℃ / sec or less, the magnetic ribbon or magnetic flake is not amorphized. In order to obtain a nano-crystallized main phase in a state where the melt is cooled (super-quenched), the cooling rate of the melt is 5×10 7 ℃ / sec or less, the melt was heated at 5×10 5 ℃ / sec or above or 1×10 6 Cooling is performed at a rate of ℃ / second or more (super rapid cooling).

[0158] If the melt can be cooled at the above speed, the method is not particularly limited, but a typical method is a liquid quenching method. A method similar to the liquid quenching method is a strip casting method. By rotating the cooling roller of the strip casting method at a higher speed than usual, the same effect as the liquid quenching method can be obtained. The liquid quenching method and the strip casting method are briefly described using the accompanying drawings.

[0159] Figure 2 This is an explanatory diagram schematically showing a cooling device used in the liquid rapid cooling method.

[0160] The liquid quenching device 50 includes a spray nozzle 51, a heater 52, and a cooling roller 53. The spray nozzle 51 is disposed opposite to the outer peripheral surface of the cooling roller 53. The molten metal is sprayed from the spray nozzle 51 to the outer peripheral surface of the cooling roller 53 rotating at a high speed, and the molten metal is cooled to obtain a magnetic thin strip 54. According to the rotation speed of the cooling roller and / or the spraying conditions, a magnetic thin sheet 55 can be obtained. Compared with the strip casting device described later, the liquid quenching device 50 can super-quench the molten metal because the molten metal is sprayed directly from the spray nozzle 51 to the outer peripheral surface of the cooling roller 53.

[0161] The molten metal may be supplied to the injection nozzle 51 , or a raw material of the molten metal may be charged into the injection nozzle 51 and the raw material may be melted by the heater 52 .

[0162] The cooling roller 53 is made of a material with high thermal conductivity such as copper or chromium, and its surface is plated with chrome to prevent corrosion by the high-temperature molten metal. The cooling roller 53 can be rotated in the direction of the arrow at a predetermined rotation speed by a driving device (not shown).

[0163] In order to cool the melt at the above speed, the circumferential speed of the cooling roller 53 may be 15 to 30 m / s. In order to prevent oxidation of the melt, etc., the atmosphere when the melt is cooled by the liquid quenching method is preferably an inert gas (inactive gas) atmosphere. The inert gas atmosphere includes a nitrogen atmosphere.

[0164] The temperature of the melt when sprayed from the spray nozzle 51 onto the outer peripheral surface of the cooling roller 53 may be 1350°C or higher, 1400°C or higher, or 1450°C or lower, and may be 1600°C or lower, 1550°C or lower, or 1500°C or lower.

[0165] Figure 3 This is an explanatory diagram schematically showing a cooling device used in the strip casting method.

[0166] The strip casting device 70 includes a melting furnace 71, a tundish 73, and a cooling roll 74. The raw materials are melted in the melting furnace 71 to prepare a molten metal 72 having the above-mentioned composition. The molten metal 72 is supplied to the tundish 73 at a certain supply amount. The molten metal 72 supplied to the tundish 73 is supplied to the cooling roll 74 from the end of the tundish 73 by the action of its own weight.

[0167] The tundish 73 is made of ceramic or the like, and can temporarily store the molten metal 72 continuously supplied from the melting furnace 71 at a predetermined flow rate, and adjust the flow of the molten metal 72 to the cooling rollers 74. The tundish 73 also has a function of adjusting the temperature of the molten metal 72 just before reaching the cooling rollers 74.

[0168] The cooling roller 74 is made of a material with high thermal conductivity such as copper or chromium, and its surface is plated with chrome to prevent corrosion by the high-temperature molten metal. The cooling roller 74 can be rotated in the direction of the arrow at a predetermined rotation speed by a driving device (not shown).

[0169] In order to obtain the above cooling speed, the circumferential speed of the cooling roller 74 may be 20 to 40 m / s.

[0170] The temperature of the melt when supplied from the end of the tundish 73 to the cooling roller 74 may be 1350°C or higher, 1400°C or higher, or 1450°C or lower, or 1600°C or lower, 1550°C or lower, or 1500°C or lower.

[0171] The molten metal 72 cooled and solidified on the outer periphery of the cooling roller 74 becomes a magnetic alloy 75 and is peeled off from the cooling roller 74 and recovered by a recovery device (not shown). The form of the magnetic alloy 75 is typically a thin strip or a thin sheet. In order to prevent oxidation of the molten metal, the atmosphere when cooling the molten metal by the strip casting method is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen atmosphere.

[0172] 〈Pressure Sintering〉

[0173] The magnetic ribbon or magnetic flake is subjected to pressure sintering to obtain a sintered body. Compared with non-pressure sintering, pressure sintering can sinter the magnetic ribbon or magnetic flake at a lower temperature and in a shorter time by applying pressure. Thus, a sintered body can be obtained without coarsening the nanocrystallized main phase and suppressing the generation of a phase with an RFe2 type crystal structure. In addition, the pressure sintering temperature is a high temperature compared with the diffusion and penetration temperature of the modified material described later. Therefore, in pressure sintering, the surface portion of the main phase and the grain boundary phase become a liquid phase, so if it is cooled rapidly after pressure sintering, it is difficult to generate a phase with an RFe2 type crystal structure.

[0174] The conditions during pressure sintering can be appropriately determined as long as the main phase is not coarsened and the generation of the phase with the RFe2 type crystal structure can be suppressed. As the pressure sintering temperature, for example, it can be above 470°C, above 500°C, above 550°C, or above 630°C, and can be below 750°C, below 700°C, below 670°C, or below 650°C. As the pressure sintering pressure, for example, it can be above 50MPa, above 100MPa, above 150MPa, above 200MPa, or above 350MPa, and can be below 600MPa, below 500MPa, below 450MPa, or below 400MPa. As the pressure sintering time, for example, it can be above 5 minutes, above 10 minutes, above 15 minutes, above 30 minutes, or above 60 minutes, and can be below 150 minutes, below 120 minutes, or below 90 minutes. After the pressure sintering is completed, the sintered body is taken out from the sintering mold and then cooled rapidly. As a result, the generation of a phase having an RFe2 type crystal structure can be suppressed. The cooling rate may be, for example, 10°C / min or more, 30°C / min or more, or 50°C / min or more, and may be 1000°C / min or less, 800°C / min or less, 600°C / min or less, 400°C / min or less, 200°C / min or less, 100°C / min or less, 80°C / min or less, or 70°C / min or less. In order to suppress the oxidation of the magnetic ribbon or magnetic sheet during pressure sintering, the pressure sintering atmosphere is preferably an inert gas atmosphere. Regarding the inert gas atmosphere, a nitrogen atmosphere is included.

[0175] The magnetic ribbon or magnetic flake having the nanocrystallized main phase is very thin, so the magnetic ribbon or magnetic flake is crushed by loading into a pressure sintering mold and / or pressure sintering operation, but the magnetic ribbon or magnetic flake can also be crushed in advance before pressure sintering. For example, a pin mill (pin mill), a cutter mill, a ball mill, and a jet mill can be used for crushing. They can also be used in combination.

[0176] 〈Thermoplastic Processing〉

[0177] The sintered body obtained by pressure sintering can be subjected to hot plastic processing. By doing so, anisotropy can be imparted to the rare earth magnet disclosed in the present invention. Hot plastic processing is performed at a temperature higher than the temperature at which a phase having an RFe2 type crystal structure is easily generated and for a short time, and the hot plastic processing is followed by rapid cooling. Therefore, the generation of a phase having an RFe2 type crystal structure can be suppressed, and coarsening of the main phase can also be avoided.

[0178] The conditions of hot plastic processing can be appropriately determined as long as they can give anisotropy to the sintered body, do not coarsen the main phase, and suppress the generation of the phase with the RFe2 type crystal structure. The hot plastic processing temperature can be, for example, 750°C or more, 770°C or more, or 790°C or more, or 850°C or less, 830°C or less, or 800°C or less. In addition, the hot plastic processing pressure can be, for example, 50MPa or more, 100MPa or more, 200MPa or more, 500MPa or more, 700MPa or more, or 900MPa or more, or 3000MPa or less, 2500MPa or less, 2000MPa or less, 1500MPa or less, or 1000MPa or less. The reduction rate can be 10% or more, 30% or more, 50% or more, or 60% or more, or 80% or less, 75% or less, 70% or less, or 65% or less. The strain rate during hot plastic working may be 0.01 / s or more, 0.1 / s or more, 1.0 / s or more, or 3.0 / s or more, and may be 15.0 / s or less, 10.0 / s or less, or 5.0 / s or less.

[0179] After the hot plastic processing is completed, the sintered body is cooled rapidly. As a result, the generation of a phase having an RFe2 type crystal structure can be suppressed. The cooling rate can be, for example, 10°C / minute or more, 30°C / minute or more, or 50°C / minute or more, or 1000°C / minute or less, 800°C / minute or less, 600°C / minute or less, 400°C / minute or less, 300°C / minute or less, 200°C / minute or less, 100°C / minute or less, or 70°C / minute or less. In order to suppress the oxidation of the sintered body during hot processing, the hot plastic processing atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen atmosphere.

[0180] 〈Preparation of modified materials〉

[0181] Prepare a modified material having the following composition, wherein the composition is represented by the formula R 2 (1-s) M 2 s In the formula representing the composition of the modified material, R 2 、M2 and s, are the same as those described in the "[Rare Earth Magnets]" section.

[0182] As a method for preparing a modified material, for example, a method of obtaining a thin strip and / or a thin sheet from a molten metal having a composition of the modified material using a liquid quenching method or a strip casting method can be cited. In this method, since the molten metal is quenched, there is less segregation in the modified material, so it is preferred. In addition, as a method for preparing a modified material, for example, it can be cited: casting a molten metal having a composition of the modified material in a mold such as a book mold. In this method, a large amount of modified material can be obtained relatively easily. In order to reduce the segregation of the modified material, the book mold is preferably made of a material with high thermal conductivity. In addition, it is preferred to perform a homogenization heat treatment on the casting material to suppress segregation. In addition, as a method for preparing a modified material, the following method can be cited: loading a raw material of the modified material into a container, arc-melting the raw material in the container, and cooling the melt to obtain an ingot. In this method, the modified material can be obtained relatively easily even when the melting point of the raw material is high. From the viewpoint of reducing the segregation of the modified material, it is preferred to perform a homogenization heat treatment on the ingot.

[0183] 〈Diffusion and penetration〉

[0184] The modifying material is diffused and infiltrated into a sintered body obtained by sintering a magnetic ribbon or a magnetic sheet. Alternatively, the sintered body obtained by sintering a magnetic ribbon or a magnetic sheet is subjected to thermoplastic processing, and the modifying material is diffused and infiltrated into the sintered body after thermoplastic processing. As a typical diffusion and infiltration method, the modifying material is brought into contact with the sintered body to obtain a contact body, and the contact body is heated to diffuse and infiltrate the melt of the modifying material into the interior of the sintered body. The melt of the modifying material passes through Figure 1 The modified material melt solidifies in the grain boundary phase 20, magnetically separating the main phases 10 from each other, thereby improving the coercive force, especially the coercive force at high temperature.

[0185] If the modified material contacts the sintered body, the form of the contact body is not particularly limited. Examples of the form of the contact body include a form in which a thin strip and / or sheet of modified material obtained by strip casting is contacted with the sintered body, or a form in which modified material powder obtained by pulverizing a strip casting material, a book mold cast material, and / or an arc-melted solidified material is contacted with the sintered body.

[0186] The diffusion and penetration conditions are not particularly limited as long as they allow the modified material to diffuse and penetrate into the interior of the sintered body, do not coarsen the main phase, and do not significantly promote the formation of a phase with an RFe2 type crystal structure. As mentioned above, the temperature region in which the coarsening of the main phase is avoided and the modified material diffuses and penetrates into the interior of the sintered body overlaps with the temperature region in which a phase with an RFe2 crystal structure is easily generated. Therefore, regarding the composition of the sintered body, that is, the composition of the molten metal prepared when obtaining the sintered body, the x and z in the formula of the overall composition of the molten metal satisfy the relationship z≤2x+0.2. The technical significance of z≤2x+0.2 has been explained in the "[Rare Earth Magnet]" section.

[0187] The diffusion infiltration temperature can be, for example, more than 550°C, more than 600°C, or more than 650°C, and can be less than 750°C, less than 740°C, less than 730°C, less than 720°C, less than 710°C, or less than 700°C. The diffusion infiltration time can be more than 30 minutes, more than 60 minutes, more than 90 minutes, or more than 120 minutes, and can be less than 300 minutes, less than 240 minutes, less than 210 minutes, less than 180 minutes, less than 165 minutes, or less than 150 minutes. After the modified material diffuses and infiltrates, the sintered body is preferably cooled rapidly. Thus, the generation of a phase having a crystal structure of the RFe2 type can be suppressed. The cooling rate may be, for example, 10°C / min or more, 30°C / min or more, or 50°C / min or more, and may be 1000°C / min or less, 800°C / min or less, 600°C / min or less, 400°C / min or less, 300°C / min or less, 200°C / min or less, 100°C / min or less, or 70°C / min or less. In order to suppress oxidation of the sintered body during diffusion infiltration, the diffusion infiltration atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen atmosphere.

[0188] When the modifying material diffuses and permeates, t mol parts of the modifying material are brought into contact with the sintered body relative to 100 mol parts of the sintered body. The value t is the same as that described in the section "[Rare Earth Magnet]".

[0189] Since the modifying material is diffused and infiltrated at a temperature at which the main phase of the sintered body does not coarsen, the average grain size of the main phase before the modifying material diffuses and infiltrates and the average grain size of the main phase after the modifying material diffuses and infiltrates are substantially within the same range. The average grain size and crystal structure of the main phase are the same as those described in the "[Rare Earth Magnet]" section.

[0190] In the diffusion and penetration of the reforming material, in order to suppress oxidation of the sintered body and the reforming material, the diffusion and penetration atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen atmosphere.

[0191] 〈Transformation〉

[0192] In addition to the contents described so far, the rare earth magnet and the method for manufacturing the same disclosed in the present invention can also be subjected to various deformations within the scope of the contents described in the claims. For example, the so-called optimal heat treatment can be performed before or after hot plastic processing, or before or after diffusion and penetration of the modified material. The so-called optimal heat treatment is a heat treatment for adjusting the structure of the rare earth magnet disclosed in the present invention, especially the structure of the grain boundary phase, which can further improve the residual magnetization, coercive force and squareness. The optimal heat treatment temperature can be, for example, above 470°C, above 550°C, or above 600°C, and can be below 750°C, below 730°C, or below 700°C. The optimal heat treatment time can be above 5 minutes, above 15 minutes, above 60 minutes, or above 120 minutes, and can be below 300 minutes, below 240 minutes, below 210 minutes, below 180 minutes, below 165 minutes, or below 150 minutes. After the optimal heat treatment is completed, the sintered body is rapidly cooled. Thus, the generation of a phase having an RFe2 type crystal structure can be suppressed. The cooling rate can be, for example, 10°C / min or more, 30°C / min or more, or 50°C / min or less, or 2000°C / min or less, 1000°C / min or less, or 500°C / min or less. In order to suppress oxidation of the magnet during the optimal heat treatment, the optimal heat treatment atmosphere is preferably an inert gas atmosphere. The inert gas atmosphere includes a nitrogen atmosphere.

[0193] Example

[0194] Hereinafter, the rare earth magnet and the method for producing the same according to the present disclosure will be described in more detail by way of examples and comparative examples. Note that the rare earth magnet and the method for producing the same according to the present disclosure are not limited to the conditions used in the following examples.

[0195] [Sample preparation]

[0196] The samples of Examples 1 to 18 and Comparative Examples 1 to 9 were prepared by the following procedure. Note that the samples of Examples 1 to 10 and Comparative Examples 1 to 4 were samples without diffusion-penetration of the modifying material, and the samples of Examples 11 to 17 and Comparative Examples 5 to 8 were samples with diffusion-penetration of the modifying material.

[0197] <Preparation of samples of Examples 1 to 10 and Comparative Examples 1 to 2 and Comparative Example 4>

[0198] Liquid quenched materials (magnetic thin ribbons) with the compositions shown in Table 1 were prepared. Figure 2The liquid quenching device 50 shown. For Examples 1 to 10 and Comparative Examples 1 to 2, the circumferential speed of the cooling roller 53 was 20 m / s. For Comparative Example 4, the circumferential speed of the cooling roller 53 was 40 m / s. After the liquid quenching material was coarsely crushed, it was pressure sintered. The cooling rate of the melt is shown in Table 1. The temperature during pressure sintering was 600°C, the pressure was 400 MPa, and the pressure sintering time was 15 minutes.

[0199] After pressure sintering, the sintered body was cooled to room temperature at a rate of 200°C / min to obtain a sintered body. The sintered body was subjected to thermoplastic processing. The thermoplastic processing temperature was 750°C, the thermoplastic processing pressure was 100 MPa, the strain rate was 0.1 / s, the reduction rate was 75%, and the cooling rate after thermoplastic processing was 300°C / min.

[0200] <Preparation of samples of Examples 11 to 18 and Comparative Examples 5 to 9>

[0201] The modifying material was diffused and infiltrated into the sintered body after the hot plastic processing and having the composition shown in Table 2. As the modifying material, Nd 0.6 Tb 0.2 Cu 0.2 The alloy of the composition of (molar ratio) was prepared, and the modifying material was diffused and infiltrated into the sintered body at 700°C for 165 minutes. The cooling rate after the diffusion and infiltration was 100°C / min. Sintered bodies after hot plastic working were prepared in the same manner as in Examples 1 to 10.

[0202] <Preparation of Samples of Comparative Examples 3 and 8>

[0203] Strip casting materials (magnetic thin strips) with the compositions shown in Table 1 were prepared. Figure 3 The strip casting device 70 shown in the figure. The peripheral speed of the cooling roller 74 is 1 m / s. The strip casting material is coarsely crushed by hydrogen embrittlement and then crushed by a jet mill to obtain magnetic powder. When the strip casting method is used to cool the melt, the cooling rate of the melt is 10 3 ℃ / sec. In addition, the particle size of magnetic powder is D 50 The magnetic powder was subjected to non-pressure sintering (non-pressure liquid phase sintering) at 1050°C for 4 hours and then cooled to room temperature at a rate of 100°C / min to obtain a sintered body. This sintered body was used as a sample of Comparative Example 3.

[0204] In the sample of Comparative Example 8, the modifying material diffused and infiltrated into the sintered body cooled to room temperature after sintering. 0.6 Tb 0.2 Cu 0.2The alloy of the composition of (molar ratio) was diffused and infiltrated into the sintered body by the reforming material at 950°C for 165 minutes. The cooling rate after the diffusion and infiltration was 1°C / min.

[0205] [evaluate]

[0206] The magnetic properties of each sample were measured at 27°C (300K) and 180°C (453K) using a vibrating sample magnetometer (VSM). The residual magnetization at 180°C was evaluated using the temperature coefficient of the residual magnetization. The temperature coefficient of the residual magnetization is a value calculated by the formula [{(residual magnetization at 180°C) - (residual magnetization at 27°C)} / (180°C - 27°C)] × 100. The smaller the absolute value of the temperature coefficient of the residual magnetization, the less the reduction in residual magnetization at high temperatures. The absolute value of the temperature coefficient of the residual magnetization is preferably less than 0.1.

[0207] Each sample was observed by SEM (Scanning Electron Microscope) to determine the average particle size of the main phase. In addition, each sample was analyzed by X-ray diffraction to determine the volume ratio of the phase with RFe2 type crystal structure, and the volume ratio of the phase with RFe2 type crystal structure to the grain boundary phase was determined using the method described in the "[Rare Earth Magnet]" section.

[0208] The results are shown in Tables 1-1 and 1-2 and Tables 2-1 and 2-2. Tables 1-1 and 1-2 show the results of the samples without diffusion-infiltrated modified materials, and Tables 2-1 and 2-2 show the results of the samples with diffusion-infiltrated modified materials. In these tables, "1-2 phase" means "a phase having a crystal structure of RFe2 type". Figure 4 This is a graph showing the demagnetization curve of the sample of Example 2. Figure 5 This is a graph showing the demagnetization curve of the sample of Comparative Example 3. Figure 6 This is a graph showing the relationship between the molar ratio x of La and the molar ratio z of Co for samples of Examples 1 to 10 and Comparative Examples 1 to 4 (samples into which the permeation modifying material was not diffused). Figure 7 This is a graph showing the relationship between the molar ratio x of La and the molar ratio z of Co for samples of Examples 11 to 17 and Comparative Examples 5 to 8 (samples in which the modifying material was diffused and infiltrated).

[0209]

[0210]

[0211]

[0212]

[0213] From Table 1-1 to Table 1-2 and Table 2-1 to Table 2-2 and Figure 4-5 It was confirmed that the samples of the examples were excellent in both squareness and residual magnetization at high temperatures. On the other hand, it was confirmed that the samples of the comparative examples were inferior in one or both of squareness and residual magnetization at high temperatures.

[0214] Depend on Figure 6 and Figure 7 It can be understood that in the region where the molar ratio x of La is less than 0.05, the sample without diffusion of the penetrating modifying material (refer to Figure 6 ) compared to the samples with diffused infiltration of modified materials (reference Figure 7 ) When the molar ratio x of La is the same, the molar ratio z of Co is small. It can be understood that a phase having a RFe2 type crystal structure is easily generated during the diffusion and penetration of the modified material, and the content ratio (molar ratio) of Co needs to be reduced in advance.

[0215] The above results confirm the effects of the rare earth magnet and the method for producing the same according to the present disclosure.

Claims

1. A rare earth magnet comprising a main phase and a grain boundary phase existing around the main phase, In terms of molar ratio, the overall composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v It indicates that, R 1 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn, and unavoidable impurity elements, and 0≤x≤0.1, 12.0≤y≤20.0, 0.15≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0, The main phase has R2Fe 14 The crystal structure of type B, where R is a rare earth element, The average particle size of the main phase is less than 1 μm, and In the grain boundary phase, the volume ratio of the phase having the RFe2 type crystal structure relative to the grain boundary phase is 0.40 or less.

2. A rare earth magnet comprising a main phase and a grain boundary phase existing around the main phase, In terms of molar ratio, the overall composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v ·(R 2 (1-s) M 2 s ) t Represents, and the whole is 100+t mole parts, wherein, R 1 and R 2 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn, and unavoidable impurity elements, M 2 For R 2 Alloyed metal elements other than rare earth elements and unavoidable impurity elements, and 0≤x≤0.1, 12.0≤y≤20.0, 0.15≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0, 0.05≤s≤0.40, 0.1≤t≤10.0, The x and the z satisfy z≤2x+0.2, The main phase has R2Fe 14 The crystal structure of type B, where R is a rare earth element, The average particle size of the main phase is less than 1 μm, and In the grain boundary phase, the volume ratio of the phase having the RFe2 type crystal structure relative to the grain boundary phase is 0.40 or less. The rare earth magnet according to claim 2 , wherein t satisfies 1.0≤t≤2.

5.

4. The rare earth magnet according to claim 2 or 3, wherein R 2 is one or more elements selected from Nd and Tb, and the M 2 It is Cu and inevitable impurity elements.

5. The rare earth magnet according to any one of claims 1 to 3, wherein the R 1 is one or more elements selected from Nd and Pr, and the M 1 It is one or more elements selected from Ga, Al and Cu, and inevitable impurity elements.

6. A method for manufacturing a rare earth magnet, which is the method for manufacturing a rare earth magnet according to claim 1, comprising the following steps: A melt having the following composition is prepared, wherein the composition is given by the formula (R 1 (1-x) La x ) y (Fe (1-z) Co z ) (100-y-w-v) B w M 1 v Indicates that, R 1 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 1 is one or more elements selected from Ga, Al, Cu, Au, Ag, Zn, In and Mn, and unavoidable impurity elements, and 0≤x≤0.1, 12.0≤y≤20.0, 0.15≤z≤0.3, 5.0≤w≤20.0, 0≤v≤2.0; The melt was heated to 5×10 5 ~2×10 6 Cooling at a rate of °C / sec to obtain a magnetic ribbon or a magnetic sheet; and The magnetic ribbon or the magnetic sheet is pressure-sintered to obtain a sintered body.

7. The method for producing a rare earth magnet according to claim 6, wherein the magnetic ribbon or the magnetic sheet is pressure-sintered at 550 to 750°C.

8. The method for manufacturing a rare earth magnet according to claim 6 or 7, further comprising the following steps: The sintered body is thermoplastic processed.

9. The method for producing a rare earth magnet according to any one of claims 6 or 7, The x and the z satisfy z≤2x+0.2, and, The following steps are also included: Prepare a modified material having the following composition, wherein the composition is represented by the formula R 2 (1-s) M 2 s Indicates that, R 2 is one or more elements selected from Nd, Pr, Gd, Tb, Dy and Ho, M 2 For R 2 Alloyed metal elements other than rare earth elements and inevitable impurity elements, and 0.05≤s≤0.40; and The modifying material is diffused and infiltrated into the sintered body.

10. The method for producing a rare earth magnet according to claim 9, wherein the diffusion-infiltration is performed at 550 to 750°C.

11. The method for producing a rare earth magnet according to claim 9, wherein the R 2 for Nd and Tb, and the M 2 It is Cu and inevitable impurity elements.

12. The method for producing a rare earth magnet according to claim 6 or 7, wherein the R 1 is one or more elements selected from Nd and Pr, and the M 1 It is one or more elements selected from Ga, Al and Cu, and inevitable impurity elements.

Citation Information

Patent Citations

  • Permanent magnet

    JP1986159708A

  • Rare-earth magnet and method for manufacturing same

    WO2014196605A1

  • Rare earth magnet and production method thereof

    CN109979699A